Analysis of Minimalist Consumption Behavior and Financial Goal Orientation as Predictors of Long-Term Savings Discipline and Budgeting in Generation Z in Jakarta - Herlin, Faradilla; Sukma Nirwana, Nihlatul Qudus; Supriandi, Supriandi (Westscience Press, 2025)
This study explores the influence of minimalist consumption behavior and financial goal orientation on budgeting practices and long-term savings discipline among Generation Z in Jakarta. Using a quantitative approach, data were collected from 150 respondents via a Likert-scale questionnaire and analyzed using Structural Equation Modeling - Partial Least Squares (SEM-PLS). The findings reveal that financial goal orientation and minimalist consumption behavior significantly impact both budgeting and savings discipline. High R2 and Q² values confirm the model’s explanatory and predictive relevance. The results underscore the importance of promoting financial goal-setting and minimalist behaviors to enhance financial management practices in Generation Z. Practical and theoretical implications are discussed, with recommendations for policymakers and educators to design targeted financial education programs.